Evaluasi Pemenuhan Hak Anak Berhadapan dengan Hukum (ABH) dalam Rehabilitasi Sosial di UPT PRSMP Surabaya: Analisis Berbasis Teori Perkembangan Remaja Santrock - Lynda Yenie Listaunsanti; Mary Philia Elisabeth (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study conducts a systematic literature review of seven selected scholarly articles and policy-related documents examining the social rehabilitation of Children in Conflict with the Law (ABH) at UPT PRSMP Surabaya. Framed within the discourse of child rights protection in institutional settings, the study explores the extent to which ABH’s fundamental rights have been substantively fulfilled. These rights include access to education, health services, religious practice, recreation, and legal protection. Using Santrock’s theory of adolescent development as an analytical lens, the review evaluates whether rehabilitation practices align with adolescents’ developmental needs. The findings indicate that rights fulfillment has been pursued through educational programs, spiritual guidance, vocational training, recreational activities, and legal assistance. Nevertheless, the synthesis identifies persistent structural challenges, notably inadequate physical facilities, incomplete legal-administrative processes, and weak inter-agency coordination. By integrating a developmental perspective into the evaluation of social rehabilitation, this study contributes to the literature by demonstrating that effective rights fulfillment extends beyond regulatory compliance to include institutional coherence and developmental sensitivity. The study concludes that while initial efforts toward fulfilling ABH rights are evident, strengthening infrastructure and improving institutional coordination are critical to enhancing the effectiveness and developmental relevance of rehabilitation programs.